2010
DOI: 10.1007/s00774-010-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the osteoblast-specific transmembrane protein IFITM5 and analysis of IFITM5-deficient mice

Abstract: Interferon-inducible transmembrane protein 5 (IFITM5) is an osteoblast-specific membrane protein whose expression peaks around the early mineralization stage during the osteoblast maturation process. To investigate IFITM5 function, we first sought to identify which proteins interact with IFITM5. Liquid chromatography mass spectrometry revealed that FK506-binding protein 11 (FKBP11) co-immunoprecipitated with IFITM5. FKBP11 is the only protein it was found to interact with in osteoblasts, while IFITM5 interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 35 publications
3
125
0
4
Order By: Relevance
“…Overexpression of IFITM5 in osteoblasts results in increased mineralization in vitro (13) and in the current study a low level of miR-762 in Saos-2 cells increased the expression of IFITM5, which may possibly contribute to hyperplastic callus formation. Furthermore, FK506-binding protein 11 (FKBP11) was identified as the only known binding partner of IFITM5 (27). Recent studies have revealed that the S-palmitoylation on IFITM5 promotes interaction with FKBP11 and cumulatively forms IFITM5-FKBP11-CD81, the prostaglandin F2 receptor negative regulator (FPRP) complex.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IFITM5 in osteoblasts results in increased mineralization in vitro (13) and in the current study a low level of miR-762 in Saos-2 cells increased the expression of IFITM5, which may possibly contribute to hyperplastic callus formation. Furthermore, FK506-binding protein 11 (FKBP11) was identified as the only known binding partner of IFITM5 (27). Recent studies have revealed that the S-palmitoylation on IFITM5 promotes interaction with FKBP11 and cumulatively forms IFITM5-FKBP11-CD81, the prostaglandin F2 receptor negative regulator (FPRP) complex.…”
Section: Discussionmentioning
confidence: 99%
“…Вероятнее всего, данный белок участвует в формиро-вании костной ткани в эмбриональном периоде. Также в исследованиях было описано, что IFITM5 участву-ет не только в формировании костной ткани, но также в формировании иммунной системы [19].…”
Section: этиологияunclassified
“…Expression levels of IFITM genes have been found to be up-regulated in gastric cancer cells and colorectal tumors [4,29]. The IFITM family potently inhibits human immunodeficiency virus type 1 (HIV-1) [23], SARS coronavirus [16], West Nile virus and dengue virus infections [12]. IFITM1 was initially cloned from a human lymphoid cell cDNA library [15], and is located on chromosome 11p15.5 [24].…”
Section: Introductionmentioning
confidence: 99%